The Quality of Life of Former Portuguese Football Players - Eduardo Teixeira; Carlos Silva; Félix Romero; João Paulo Costa; António Vicente (MDPI AG, 2024)
Background: The demands of playing professional football can have an impact on an individual's quality of life (QoL), which may remain into retirement. Given limited evidence exists regarding the QoL in former football players, this study aimed to assess QoL among Portuguese former players according to career duration, career end period, competitive level, tactical-positional status, international status, academic qualifications, serious injuries in career, and current professional football connection. Methods: The study included 84 Portuguese former football players (48.8 ± 8.2 years old) who transitioned to retirement between 1988 and 2018. The WHOQOL-BREF questionnaire was used to assess QoL perceptions, and the Portuguese version was validated. Results and Discussion: The former players have positive QoL indicators, both in general and across the four domains, namely in terms of the physical, psychological, and social relationship and environment. There were no statistically significant differences in QoL between the defined categories for career end period, competitive level, tactical-positional status, international status, and current professional football connection. Likewise, there was no significant correlation between QoL and career duration. In contrast, there were significant differences in general QoL (p < 0.023) and in the physical domain (p < 0.001) between former players with different academic qualifications. A significant correlation was found between the number of severe injuries sustained in a career and QoL in the physical domain (R = −0.300, p = 0.006). Conclusions: There are no concerning QoL results presented by former players. However, the number of severe injuries sustained during the career was associated with a lower QoL, while holding higher academic qualifications demonstrated higher general and physical QoL. Studies with larger samples should be conducted to confirm these trends.